Viruses That Can and Cannot Coexist With Humans and the Future of SARS-CoV-2 - Furuse, Yuki; Oshitani, Hitoshi (Frontiers in Microbiology, 2020)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has become a worldwide pandemic. Many projections concerning the outbreak, such as the estimated number of cases and deaths in upcoming months, have been made available. However, what happens to the virus after the pandemic subsides has not been fully explored. In this article, we discuss the ways that past and present human viruses have emerged via zoonotic transmission, the mechanisms that they have acquired the ability for effective transmission among humans, the process to sustain a chain of transmission to coexist with humans, and the factors important for complete containment leading to eradication of viruses. These aspects of viral disease may provide clues for the future path that SARS-CoV-2 might take in relation to human infection.